2022
DOI: 10.1111/age.13174
|View full text |Cite
|
Sign up to set email alerts
|

Identification of processed pseudogenes in the genome of Thoroughbred horses: Possibility of gene‐doping detection considering the presence of pseudogenes

Abstract: Processed pseudogenes, also known as retrocopy genes, are copies of messenger RNAs that have been reverse transcribed into DNA and inserted into the genome. In this study, we identified 62 processed pseudogene candidates as intron‐less genes from whole‐genome sequencing (WGS) data of Thoroughbred horses using delly structural variation software. The 62 processed pseudogene candidates were confirmed by PCR amplification of intron‐less products. A total of 11 processed pseudogenes were confirmed in the genome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…High INDEL density was observed on chromosomes 12 and 20. Previous studies observed a similar trend on the same chromosomes for SNVs and nonsynonymous substitutions [ 7 , 16 ]. Although the exact reason for this is unknown, one reason is thought to be the existence of metabolic and sensory perception regions on chromosome 12, and immune response and antigen-processing regions on chromosome 20 [ 18 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…High INDEL density was observed on chromosomes 12 and 20. Previous studies observed a similar trend on the same chromosomes for SNVs and nonsynonymous substitutions [ 7 , 16 ]. Although the exact reason for this is unknown, one reason is thought to be the existence of metabolic and sensory perception regions on chromosome 12, and immune response and antigen-processing regions on chromosome 20 [ 18 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 73%
“…It was confirmed that 779,457 loci (49.8%) were novel INDELs by comparing them with the Ensembl (Release 108). Our current and previous studies [ 7 , 16 ] identified 12 million SNVs, 1.56 million short INDELs, and 62 processed pseudogenes in 101 Thoroughbred horses. Although Thoroughbreds were bred as a closed population from a small founder population, it was demonstrated that current Thoroughbred populations have diverse genome structures.…”
Section: Discussionmentioning
confidence: 74%
“…100 However, there may be a risk of false positives using these methodologies if there is an intron-less "pseudogene" in the horse's genome, which corresponds to the transgene of interest. 101 An alternative method for detection of transgenic horses produced via SCNT proposes using whole-mitochondrial sequencing via tiled long-range PCR and NGS to detect differences in mitochondrial DNA between a transgenic horse and the registered dam. 102 The aforementioned studies were performed in vitro or in silico and to date, no studies have been carried out using transgenic animals or embryos.…”
Section: In Vivo Raav Gene Therapy In Horsesmentioning
confidence: 99%
“…A database of rare and common genetic variants in Thoroughbred horses has been established for the purpose of non‐targeted detection of transgenic equids 100 . However, there may be a risk of false positives using these methodologies if there is an intron‐less “pseudogene” in the horse's genome, which corresponds to the transgene of interest 101 . An alternative method for detection of transgenic horses produced via SCNT proposes using whole‐mitochondrial sequencing via tiled long‐range PCR and NGS to detect differences in mitochondrial DNA between a transgenic horse and the registered dam 102 .…”
Section: Introductionmentioning
confidence: 99%
“…NGS technology has also enabled whole-genome resequencing of species with reference genome sequences [ 24 , 25 , 26 ]. Using NGS, transgenes can be detected as deletions of introns [ 27 , 28 , 29 ], enabling screening for nontargeted transgenes by comparing the detected intron deletions to annotated gene information (i.e., the intron location in reference sequences). Amplicon sequencing to detect targeted genes using NGS has also been developed for transgene detection [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%